Thermogravimetric, thermochemical, and infrared spectral characterization of feedstocks and biochar derived at different pyrolysis temperatures. (August 2018) - Li, Simeng; Chen, Gang
Graphical abstract: Highlights: Pyrolysis temperature was the dominating factor affecting biochar properties. Properties of biochar from different feedstocks responded to temperature similarly. Proposed carbon-based recalcitrance index showed advantages over the current index. Multiple characterization techniques evidenced better suitability of the new index. Feedstock pretreatment was the costliest process during the biochar production. Abstract: Biochar is a promising biomass product for soil amendment, remediation, and carbon sequestration. In this study, the effect of pyrolysis temperature and feedstock type on biochar physiochemical properties including stability, recalcitrance, and surface functionality were investigated through thermogravimetric, thermochemical, and infrared spectral analyses. It is concluded in this research that pyrolysis temperature was the dominating factor determining the inherent characteristics of the derived biochar. High-temperature pyrolysis (≥600 °C) derived the biochar with a high pH, stability, recalcitrance, and higher heating value (HHV). On the other hand, the biochar produced from low-temperature pyrolysis (≤400 °C) had a larger mass yield, energy recovery, more volatile content, and diverse surface functional groups. The different biochar characteristics will lead to different agricultural and environmental applications. Also in this research, a carbon-based recalcitrance index (R50, C ) based on a novel multi-element scanning thermal analysis (MESTA) was proposed to improve the current recalcitrance index (R50 ) based on the conventional thermogravimetric analysis (TGA) for the evaluation of biochar's carbon sequestration potential. The direct comparison of the two indexes, as well as the results from the infrared spectral analysis and ultimate analysis, indicated that R50, C was better at characterizing biochar's recalcitrance, especially when the mineral content of the feedstock was high. In addition, the cost breakdown indicated that the pretreatment of feedstock was the costliest process during biochar production.